Pengaruh Labelisasi Halal Dan Citra Merek Terhadap Keputusan Pembelian Konsumen Pada Produk Ms Glow Di Kabupaten Kolaka - Almansyah Rundu Wonua; Niar Astaginy; Rita Saputri (JURNAL RISET MANAJEMEN (JURMA), 2023)
This study aims to determine: (1) The Effect of Halal Labeling on Consumer Purchase Decisions on Ms Glow Products in Kolaka Regency and (2) The Effect of Brand Image on Consumer Purchase Decisions on Ms Glow Products in Kolaka Regency. This research is a quantitative research using an explanatory research model using a questionnaire as an instrument. The population in this study were respondents who had bought or used Ms glow products and respondents who used Ms glow products with a total sample of 120 respondents using a purposive sampling technique. Data collection techniques are primary data and secondary data. Testing the research instrument used the validity test and reliability test with SPSS 25. The research data analysis technique used the Structural Equation Modeling (SEM-PLS) method with SmartPLS 3.0. Based on the research results, it is known that Halal Labeling has a positive and significant effect on Purchase Decisions. This is evidenced by the t-count or t-statistic, which is 2.234, which is higher than the t-table value, which is> 1.657. With p-values ​​of 0.027. Meanwhile, brand image also has a positive and significant effect on purchasing decisions because the t-count or t-statistic value is 8.123 which is higher than the t-table value, which is > 1.657. With P-values ​​of 0.000. Then Halal Labeling and Brand Image have a positive and significant effect on Purchase Decision of 80.0%.